Branched morphology of Nb powder particles fabricated by calciothermic reduction in CaCl2 melt. (November 2017) - Suzuki, Nobuyoshi; Suzuki, Ryosuke O.; Natsui, Shungo; Kikuchi, Tatsuya
Abstract: A new branched morphology of metallic niobium powder particles was produced by calciothermic reduction of niobium oxides in molten CaCl2 . The influence of some reaction parameters on the powder particle morphology was studied, and the formation mechanism was investigated. It was found that the formation of intermediate complex niobium oxides (Cax Nb2 Oy ) was crucial in the formation of niobium powder particles with the branched morphology. Based on this finding, the formation mechanism of the branched morphology in four stages was proposed. These Nb powder particles with microscopic branches can prevent particle sintering during the fabrication process of electric capacitors, allowing the latter to exhibit a higher capacitance. Graphical abstract: Highlights: A branched morphology of metallic Nb particles was produced in molten CaCl2 . Calciothermic reduction of Nb2 O5 via plate-like Cax Nb2 Oy crystals is crucial. Nb branches prevent particle sintering during fabrication of electric capacitors.